Pengaruh Pengayaan Jenis Media Tanam Dengan Penambahan Limbah Teh Terhadap Pertumbuhan dan Hasil Tanaman Melon (Cucumis melo L.) Var.Alisha F1 Dengan Sistem Irigasi Tetes - Allya Salsabila; Bastaman Syah; Rommy Andhika Laksono (Universitas Respati Indonesia, 2025)
There was a decline in melon production in 2021–2022 due to suboptimal cultivation practices in land management and limited land availability resulting from the conversion of agricultural land. This issue can be addressed through the use of a hydroponic system and appropriate growing media. This study aimed to determine the best enrichment of growing media with the addition of tea waste to support the growth and yield of melon plants. The research method used was a Completely. The research was conducted using a single-factor Randomized Complete Block Design (RCBD) consisting of 10 treatments, each replicated three times. The treatments included: A (Cocopeat + Zeolite 1:1), B (Cocopeat + Zeolite 1:1 + 100 g Tea Waste), C (Cocopeat + Zeolite 1:1 + 200 g Tea Waste), D (Cocopeat + Zeolite 1:1 + 300 g Tea Waste), E (Cocopeat + Zeolite 1:1 + 400 g Tea Waste), F (Cocopeat + Fern Roots 1:1), G (Cocopeat + Fern Roots 1:1 + 100 g Tea Waste), H (Cocopeat + Fern Roots 1:1 + 200 g Tea Waste), I (Cocopeat + Fern Roots 1:1 + 300 g Tea Waste), and J (Cocopeat + Fern Roots 1:1 + 400 g Tea Waste). The results showed that the enrichment of growing media with tea waste had a significant effect on plant height, leaf number, stem diameter, fruit weight per plant, fruit circumference, flesh thickness, and sweetness level of the melon fruit. The best results were observed in treatment J, which produced the highest values across all parameters, including a plant height of 144.90 cm and a fruit sweetness level of 15.66 °Brix.